Post-war Agriculture in Żuławy versus Changes in the Region’s Cultural and Social Landscape in Source Materials, Diaries and Farmers’ Narratives - Aleksandra Paprot-Wielopolska (Wieś i Rolnictwo)
On the example of Żuławy, the paper discusses questions connected with postwar migrations to the Polish Western and Northern Territories, and their consequences for agriculture. It focuses on issues related to the development of the region by new settlers and the changes taking place in the cultural and social landscape. The text highlights the region’s character and its economic conditions before 1945, and considers agricultural settlement and the agrarian and social structure after 1945. Post-war agriculture in the region is presented in the light of the cultural heritage described in scientific literature, the first settlers’ recollections written in the form of diaries in the early 1970s, and biographical accounts that the author recorded in Żuławy in 2018.